The Effect Of Product Quality, Price And Promotion On Customer Satisfaction Of Honda Scoopy Motorcycles With Purchase Decisions As Intervening Variables At Honda Mina SPN Dealership, Ranah Batahan District - Septriana Sari; M. Hamid; Romia Romia (CV. AFDIFAL MAJU BERKAH, 2025)
The results of this research are There is a significant influence of product quality on the decision to purchase a Honda Scoopy motorbike at the Mina Spn Motor Dealer. There is a significant influence of price on the decision to purchase a Honda Scoopy motorbike at the Mina Spn Motor Dealer. There is a significant influence of promotion on the decision to purchase a Honda Scoopy motorbike at the Mina Spn Motor Dealer. There is a significant influence of product quality on customer satisfaction for Honda Scoopy motorbikes at the Mina Spn Motor Dealer. There is a significant influence of price on customer satisfaction for Honda Scoopy motorbikes at the Mina Spn Motor Dealer. There is a significant influence of promotion on customer satisfaction for Honda Scoopy motorbikes at the Mina Spn Motor Dealer. There is an insignificant influence on purchasing decisions on customer satisfaction for Honda Scoopy motorbikes at the Mina Spn Motor Dealer. There is an insignificant influence of product quality on customer satisfaction through the decision to purchase a Honda Scoopy motorbike at the Mina Spn Motor Dealer. There is an insignificant influence of price on customer satisfaction through the decision to purchase a Honda Scoopy motorbike at the Mina Spn Motor Dealer. There is an insignificant effect of promotion on customer satisfaction through the decision to purchase a Honda Scoopy motorbike at the Mina Spn Motor Dealer